Pengaruh Manajemen Kas, Manajemen Piutang, Dan Manajemen Persediaan Terhadap Profitabilitas Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Iva Aulia Fajrin,; Sunu Priyawan, (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to test the influence of Cash Management, Accounts Receivable Management and Inventory Management on Profitability in Indonesian Food and Beverage Subsector Manufacturing companies registered in Indonesia in the period 2020-2022. The population used is 35 Manufacture companies of the Food and Beverage subsector registered in Indonesia. Sample determination is carried out using the purposive sampling method approach, based on sample determination criteria that have been carried out by 20 companies during the period 2020-2022. The study also uses quantitative approaches and techniques of multiple linear regression analysis, correlation analysis and coefficient of determination, as well as hypothesis tests using T test and F test previously performed classical assumption test first. The result of this study is that simultaneously the influence of cash management (X1), accounts receivable management (X2), inventory management (X3) on profitability (Y) obtained Fcompat (3,680) is greater than Ftable (2,680) 76). This indicates that simultaneously Cash management (X1), Accounts receivable management (X2), Inventory management (X3) against profitability (Y). The test results partially show that there is a positive and significant influence on inventory management on profitability. Cash management and accounts receivable have a negative and insignificant effect on profitability.